What drives thesis advisor selection in the post-pandemic context? Evidence from a quantitative study - Wijayati, Rifky Dora; Tarnoto, Nissa (Universitas Ahmad Dahlan, 2026)
The COVID-19 pandemic disrupted thesis advising practices in an English Language Education program at a private university, limiting interaction and communication between students and advisors. However, limited research has examined how these disruptions have reshaped students’ preferences in selecting thesis advisors in the post-pandemic context. Addressing this gap, this study aims to identify the key factors that drive students’ choices of thesis advisors and provide insights for improving advising practices. Data from 75 students were collected via an online survey and analyzed using descriptive and inferential statistics (correlation and ANOVA). The analysis focuses on five dimensions: subject matter expertise, access to academic resources, publication record and research productivity, teaching and supervisory experience, and communication quality. The findings indicate that subject matter expertise and access to relevant academic resources are the primary drivers of advisor selection. Publication record and research productivity also emerge as significant indicators of academic credibility, while supervisory experience in English Language Teaching (ELT) remains important. The findings suggest a shift toward prioritizing academic competence and research support, reflecting students’ adaptation to more independent and resource-driven learning environments. These results highlight the need for universities to strengthen research capacity, improve access to academic resources, and develop more responsive hybrid advising strategies.